Internal Control and Financial Reporting Quality: A Sharia Accountability Perspective at BAZNAS Garut Regency - Ujang Burhanudin; Diana Farid; Sofyan Mei Utama (Journal of Islamic Economics and Business, 2025)
This study aims to analyze the influence of internal control on the quality of financial statements at BAZNAS Garut Regency by emphasizing the perspective of sharia accountability. Zakat institutions are required to implement transparent and accountable governance, but previous research has shown mixed results regarding the relationship between internal control and the quality of financial statements. Therefore, this study provides a contextual study of zakat institutions that have special characteristics in the management of people's funds.This study uses a descriptive quantitative approach by distributing questionnaires to Amil and staff who are directly involved in financial management at BAZNAS Garut. Data were analyzed descriptively to measure respondents' perception of the implementation of the five components of internal control (control environment, risk assessment, control activities, information and communication, and monitoring) and the quality of financial statements based on the characteristics of relevance, reliability, comparability, and comprehension. The results of the study show that internal control at BAZNAS Garut has been running well, especially in the aspects of the control environment and control activities. However, there are still weaknesses in the aspects of monitoring and accounting information systems. Financial statements are considered relevant and reliable, although some respondents consider the use of sharia accounting terms still difficult for the general public to understand. This research emphasizes the importance of internal control in producing quality financial reports, in line with Sharia Enterprise Theory and stewardship theory which emphasizes vertical accountability to Allah SWT and horizontal to society.